Hairpin RF resonators for MR imaging transceiver arrays with high inter-channel isolation and B1 efficiency at ultrahigh field 7 T - Payne, Komlan; Ying, Leslie L.; Zhang, Xiaoliang (Journal of magnetic resonance (1997), 2022)
[Display omitted] •The quest for higher SNR and thus higher spatial resolution has enabled the study of MRI at ultra-high fields.•Hairpin high-impedance RF coil design provides prominent decoupling capability and high B1 efficacy for transceive RF arrays.•High-impedance RF coils can achieve high electromagnetic decoupling among elements in high-density transceiver RF arrays.•The elimination of lumped inductors in RF coil resonant circuits increases the B1 field efficiency in imaging subjects. Electromagnetic decoupling among a close-fitting or high-density transceiver RF array elements is required to maintain the integrity of the magnetic flux density from individual channel for enhanced performance in detection sensitivity and parallel imaging. High-impedance RF coils have demonstrated to be a prominent design method to circumvent these coupling issues. Yet, inherent characteristics of these coils have ramification on the B1 field efficiency and SNR. In this work, we propose a hairpin high impedance RF resonator design for highly decoupled multichannel transceiver arrays at ultrahigh magnetic fields. Due to the high impedance property of the hairpin resonators, the proposed transceiver array can provide high decoupling performance without using any dedicated decoupling circuit among the resonant elements. Because of elimination of lumped inductors in the resonator circuit, higher B1 field efficiency in imaging subjects can be expected. In order to validate the feasibility of the proposed hairpin RF coils, systematical studies on decoupling performance, field distribution, and SNR are performed, and the results are compared with those obtained from existing high-impedance RF coil, e.g., “self-decoupled RF coil”. To further investigate its performance, an 8-channel head coil array using the proposed hairpin resonators loaded with a cylindrical phantom is designed, demonstrating a 19 % increase of the B1+ field intensity compared to the self-decoupled coils at 7 T. Furthermore, the characteristics of the hairpin RF coils are evaluated using a more realistic human head voxel model numerically. The proposed hairpin RF coil provides excellent decoupling performance and superior RF magnetic field efficiency compared to the “self-decoupled” high impedance coils. Bench test of a pair of fabricated hairpin coils prove to be in good accordance with numerical results.